Expansion of Gammadelta T Cells from Cord Blood: A Therapeutical Possibility - Sofia Berglund; Ahmed Gaballa; Piamsiri Sawaisorn; Berit Sundberg; Michael Uhlin (Hindawi Limited, 2018)
Gammadelta (γδ) T cells are found in both blood and tissues and have antiviral and antitumor properties. The frequency of γδ T cells in umbilical cord blood (UCB) is low, and the majority express δ1, in contrast to blood, whereas the main subset is δ2γ9 T cells. UCB γδ T cells are functionally immature, which together with their scarcity complicates the development of UCB γδ T cell therapies. We aimed to develop an effective expansion protocol for UCB γδ T cells based on zoledronate and IL-2. We found that culture with 5 μM zoledronate and 200 IU IL-2/ml medium for 14 days promoted extensive proliferation. The majority of the cultured cells were γ9δ2 T cells. The fold expansion of this, originally infrequent, subset was impressive (median and maximum fold change 253 and 1085, resp.). After culture, the cells had a polyclonal γδ T cell repertoire and the main memory subset was central memory (CD45RO+ CD27+). The cells produced cytokines such as IL-1B, IL-2, and IL-8 and displayed significant tumor-killing capacity. These results show that development of in vitro expanded UCB γδ T cell therapies is feasible. It could prove a valuable treatment modality for patients after umbilical cord blood transplantation.